Assessing Safe Discharge Criteria for Pediatric Oncology Patients Admitted for Febrile Neutropenia. Issue 6 (August 2021) - Huschart, Emily; Ducore, Jonathan; Chung, Jong
Abstract : Recent studies suggest outpatient therapy, oral antibiotics, or earlier discharge could be appropriate in some pediatric patients admitted with febrile neutropenia; supporting data are lacking. Retrospective chart review of patients admitted from September 2005 through October 2016 identified 131 "early discharge" febrile neutropenia admissions with discharge absolute neutrophil count (ANC) <500/µl and negative cultures. All were afebrile and discharged without outpatient antibiotics. Eleven of 131 patients (8%) were readmitted. Two patients called back for late positive cultures. Nine were readmitted with febrile neutropenia; 2 had positive cultures on readmission. All 4 patients with positive cultures were safely treated with appropriate antibiotics. The remaining 7 patients had uneventful readmissions. Average ANC (SD) at discharge was lower for patients readmitted versus those not readmitted (69 [70] vs. 196 [145], P ⩽0.001), as was absolute phagocyte count (APC) at discharge (97 [82] vs. 453 [431], P ⩽0.001). APC on admission was not significantly lower for those readmitted (165 [254] vs. 321 [388], P =0.09). Few patients required readmission; those with bacterial infections were easily identified and appropriately treated. Higher ANC or APC criteria for discharge would increase length of hospital stay without decreasing morbidity. A subset of patients admitted with febrile neutropenia can be safely discharged before count recovery without oral antibiotics.